Accuracy of Self-reported Weight in Hispanic/Latino Adults of the Hispanic Community Health Study/Study of Latinos. Issue 6 (November 2017) - Fernández-Rhodes, Lindsay; Robinson, Whitney R.; Sotres-Alvarez, Daniela; Franceschini, Nora; Castañeda, Sheila F.; Buelna, Christina; Moncrieft, Ashley; Llabre, Maria; Daviglus, Martha L.; Qi, Qibin; Agarwal, Anita; Isasi, Carmen R.; et al.
Abstract : Background: Previous US population–based studies have found that body weight may be underestimated when self-reported. However, this research may not apply to all US Hispanics/Latinos, many of whom are immigrants with distinct cultural orientations to ideal body size. We assessed the data quality and accuracy of self-reported weight in a diverse, community-based, US sample of primarily foreign-born Hispanic/Latino adults. Methods: Using baseline data (2008–2011) from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL), we described the difference between contemporaneous self-reported and measured current body weight (n = 16, 119) and used multivariate adjusted models to establish whether the observed trends in misreporting in potential predictors of inaccuracy persisted after adjustment for other predictors. Last, we described the weighted percentage agreement in body mass classification using either self-reported or measured weight (n = 16, 110). Results: Self-reported weight was well correlated with ( r 2 = 0.95) and on average 0.23 kg greater than measured weight. The range of this misreporting was large and several factors were associated with misreporting: age group, gender, body mass categories, nativity, study site by background, unit of self-report (kg or lb), and end-digit preference. The percentage agreement of body mass classification using self-reported versus measured weight was 86% and varied across prevalent health conditions. Conclusions: The direction of misreporting in self-reported weight, and thus the anticipated bias in obesity prevalence estimates based on self-reported weights, may differ in US Hispanic/Latinos from that found in prior studies. Future investigations using self-reported body weight in US Hispanic/Latinos should consider this information for bias analyses. See video abstract at, http://links.lww.com/EDE/B276 . Abstract : Supplemental Digital Content is available in the text.